2014
DOI: 10.1177/0003489414557019
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Submandibular Ganglion Neurectomy

Abstract: Transoral submandibular neurectomy is an attractive addition to the armamentarium of surgical options for the treatment of medically intractable sialorrhea. Further study in selected patients would need to be performed to demonstrate clinical feasibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The length, width, and height of submandibular ganglion were 2.66 mm, 1.74 mm, and 3.63 mm respectively. The submandibular ganglion was found in the lingual nerve tract on the posterior aspect of the mylohyoid muscle, similar to that shown in another study [ 16 ]. The lingual nerve was tracked in a reverse manner.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The length, width, and height of submandibular ganglion were 2.66 mm, 1.74 mm, and 3.63 mm respectively. The submandibular ganglion was found in the lingual nerve tract on the posterior aspect of the mylohyoid muscle, similar to that shown in another study [ 16 ]. The lingual nerve was tracked in a reverse manner.…”
Section: Resultssupporting
confidence: 89%
“…Kim, et al was found in the lingual nerve tract on the posterior aspect of the mylohyoid muscle, similar to that shown in another study [16]. The lingual nerve was tracked in a reverse manner.…”
Section: ) Submandibular Ganglionsupporting
confidence: 79%
See 2 more Smart Citations
“…Spock et al sought to manage sialorrhea via transoral submandibular neurectomy; the authors studied the feasibility of the technique employing cadavers . The procedure was attractive in that it was minimally invasive, highly selective, and feasible.…”
Section: Discussionmentioning
confidence: 99%